Mental Health Challenges in Elite Sport: Balancing Risk with Reward - Judy Van Raalte (Frontiers Research Topics, 2018)
Elite sport typically provides obvious rewards in terms of recognition, finance and acclaim for athletic performance. Increasingly, we are becoming aware of the risks that elite athletes, their entourage, including families, sport-science support team and coaches are exposed to. Twelve original articles, seven commentaries and a corrigendum, are structured in a five chapter format. Chapter 1, comprising the Editorial is titled "An Overview of Mental Health in Elite Sport: Changing the Play Book" to reflect the advocacy role of this article. Chapter 2 ("Finding the Sweet Spot") amplifies the voice of key stakeholders across three qualitative studies with three additional commentaries. Quantitative evidence is presented in Chapter 3 which has the sub-title the "State of Play." Chapter 4, entitled the "Field of Play" includes three original publications which present contrasting conceptual approaches to guide researchers in hypothesis generation, formulation and implementation science. Finally, in Chapter 5, "Seeing the Ball Early" prospective perspectives are provided in three publications reinforced by two commentaries. The future thinking ideas includes the use of virtual reality training, a broadening of the concept of mental health literacy, tackling stigma and focusing on the potential positive effect of the natural environment on well-being and recovery.To date the research topic has generated widespread in the field. For example, several articles have generated an Altmetric score above 40 with one publication meriting an Altmetric score of 102. We envisage that the impact of this e-book will not simply be measured in citations, views, downloads nor social media impact, but in the discourse that emerges from this collection of contributions from a combined total of 53 authors from across three continents. It is our hope that this e-book, providing a snapshot of global challenges for elite athletes mental health and well-being, becomes a touchstone for researchers and practitioners in the field.